A clinical case of STEMI in a 19-year-old woman with hypercholesterolemia - S. Barakova; B. Grigorova; E. Pashkuleva-Dermenjieva; N. Ivanov; P. Moraliyska; P. Lazarov; A. Gamisheva (Българска кардиология)
We present a clinical case of a 19-year-old young woman who was admitted to the Emergency Department of the Medical Military Academy in September 2023 with complaints of palpitations, nausea, vomiting, a shortness of breath and a previous syncope. After the conducted clinical, laboratory and instrumental tests, an acute myocardial infarction (AMI) with ST-elevation (STEMI) was established in the presence of increased levels of total (TC) and low-density cholesterol (LDL) and triglycerides (TG). There was no indication of hypercholesterolemia up to this point from the anamnesis. The case is interesting because of the young age of the patient, which suggests familial hypercholesterolemia (FH) as a risk factor (RF) for atherogenesis in the absence of other RF, such as diabetes mellitus (DM) and arterial hypertension (AH).